Small Scale Wind Generation System: Part II – A Novel Quasi-Z-Source Inverter and FRG-QZSI-Micro Grid Interface - M. Ramkumar; K. N. Srinivas (Institute of Advanced Engineering and Science, 2017)
This paper proposes modelling, analysis and control of a small scale wind energy conversion system employing a direct driven Flux Reversal Generator (FRG) connected to the micro grid through a quasi-Z-source inverter (QZSI). This entire research is made up of two major parts viz., FRG and QZSI. In the part I report of this research work, the role of FRG has been thoroughly modelled and verified. In this part II, the modelling and analysis of QZSI for this purpose is presented. In addition, the modified space vector PWM (SVPWM) technique is proposed in this paper to satisfy the shoot-through characteristic of QZSI, which is a novel. The interface of FRG and QZSI to inject power in to micro grid has been finally presented. The simulation results are validated with the analytical results. Section I discusses the open loop control of QZSI. The mathematical modelling of QZSI for this purpose is given and analytically validated. This flowed by section II in which the proposed SVPWM is presented. The procedure to obtain triggering pulses using this proposed modulation technique is discussed. Section III presents closed loop control strategies for QZSI. Section IV presents the micro gridinte face and power injection.